The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4103/jfmpc.jfmpc_378_18
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of holistic group health promotion program on educational stress, anxiety, and depression among adolescent girls – A pilot study

Abstract: Background: Academic stress is one of the major stresses among adolescents and it has been associated with poor mental health. Aim: Evaluate effectiveness of holistic intervention on educational stress among adolescent girls. Materials and Methods: Randomized controlled design was adopted and study was conducted at selected colleges of Dharwad city, India. 60 adolescent girls were randomly assigned to either experimental or control group. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
(34 reference statements)
3
15
0
3
Order By: Relevance
“…The study also revealed that the children, whose parents feel anxiety for their children, perform well in their academic achievements and vice versa. Rentala et al, (2019) conducted a study to find the relationship between parental anxiety, academic stress, and academic achievement in a private higher secondary school. The participants of this study were 400 young students.…”
Section: Parental Anxiety and Students' Academic Stressmentioning
confidence: 99%
“…The study also revealed that the children, whose parents feel anxiety for their children, perform well in their academic achievements and vice versa. Rentala et al, (2019) conducted a study to find the relationship between parental anxiety, academic stress, and academic achievement in a private higher secondary school. The participants of this study were 400 young students.…”
Section: Parental Anxiety and Students' Academic Stressmentioning
confidence: 99%
“…To achieve this objective, school management teams should assist in developing strategies that can best help depressed adolescents in their recovery (Thomson 2018:39). Furthermore, Rentala et al (2019Rentala et al ( :1082 argued that adequate school health education programmes improve depressive symptoms and other mental health related conditions in adolescents.…”
Section: Theme 1: Comprehensive Psychosocial Managementmentioning
confidence: 99%
“…Literature shows that academic pressure causes various mental and behavioral disorders like depression, frustration, anxiety, helplessness, and suicidal behavior; these are more common emotional disorders in adolescents. [1] Somatic symptom disorder Somatic comes from soma, the Greek word for body [2] Somatic symptom disorders are characterized by physical symptoms suggesting medical disease, but without demonstrable organic pathology or known patho-physiological mechanism to account for them. [3] The Somatic symptom related disorders include Somatic symptom disorder, factitious disorder, Hypochondriasis, conversion disorders, and psychological factors affecting other medical conditions.…”
Section: Marilyn Van M Derbur Miss America By Daymentioning
confidence: 99%